The role of reality enhancing technologies in teaching and learning of mathematics. (September 2021) - Buentello-Montoya, D.A.; Lomelí-Plascencia, M.G.; Medina-Herrera, L.M.
Highlights: AR and VR have been successfully used to improve the student's performance. A challenge for AR and VR lies in the digital literacy of teachers and students. AR and VR require user's prior preparation to be exploited at its fullest. The use of AR and VR in education might globally increase over the coming years. Abstract: Virtual and Augmented Reality (VR and AR, respectively) are technologies with potential impact in education, and can facilitate subjects, such as mathematics, that may be difficult for students. This manuscript presents a comprehensive review of works using VR and/or AR for teaching mathematics at all academic levels during the timespan from 2015 to June 2020. The work contributes by providing an overview of the findings, challenges, and trends for the use of these technologies. Results from the review indicate that both VR and AR have seen acceptance by students but using the technologies might be complicated if lectures are not designed adequately. Moreover, the number of publications involving AR and VR in teaching and learning maths has increased over time, and the demographics indicate that the technology is taking prevalence in developing countries. Graphical abstract: Image, graphical abstract